Single implant with immediate function after extraction: case report (Research, Society and Development, 2021)
The rehabilitation of a patient with some type of tooth loss must be carried out as quickly as possible, thus causing fewer aesthetic and functional problems for the patient. Dental implants with immediate function are an excellent alternative to reduce the waiting time for rehabilitation in relation to the conventional technique, with the prosthesis being placed soon after the installation of the implant, with results similar to those of the conventional technique. In addition, there is greater preservation of the peri-implant bone as well as the gingival contour. One of the indications for using the technique is when dental fracture occurs. Therefore, the objective of this study was to describe the technique performed in a clinical case, in which the patient was rehabilitated with an implant in immediate function, after the fracture of the upper first premolar, removing element 24 and installing 1 implant. The technique used was bone expansion together with a graft to fill the GAP. By obtaining a torque of 45N.cm, it was possible to re-establish the immediate function and aesthetics of the region. It was concluded that immediate function with the use of dental implants after extraction is possible, being a favorable technique that provided success in rehabilitation, returning immediate function and esthetics to the patient.